Analisis Komparatif Rasio Keuangan dan Valuasi AKRA vs ANTM : Implikasi Investasi (2019–2023) - Rahmat Burhamzah; A. Reski Almaida Dg Macenning (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
This research aims to conduct an in-depth comparative analysis of the financial ratios and valuations between PT Aneka Tambang Tbk (ANTM), driven by commodity cycles, and PT AKR Corporindo Tbk (AKRA), a stable logistics company, over the volatile 2019–2023 period. Using a quantitative descriptive comparative approach, the study analyzed time-series trends and cross-sectional comparisons of Profitability (ROE), Solvency (DER), and Valuation (EPS, PER, PBV) ratios. The findings indicate that ANTM possessed significantly superior capital efficiency, evidenced by an exceptional Return on Equity (ROE) of 98.75% in 2023, but concurrently bore much higher debt risk (DER 375%) compared to AKRA (ROE 19.70%, DER 115.30%). Conversely, AKRA was valued cheaper based on both PER (10.47) and PBV (2.11) compared to ANTM's premium valuation (PER 13.31, PBV 13.14). The clear investment implication suggests ANTM is a high-risk, cyclical stock with exceptional return potential, while AKRA represents a more stable choice with lower solvency risk and fair valuation.